1978
DOI: 10.1093/iat/3.1.143
|View full text |Cite
|
Sign up to set email alerts
|

Smaller European Elm Bark Beetle Panel Tests, 1975

Abstract: Plywood panels (15 x 15 cm) were treated with 8 insecticides from June 23-27, 1975, to determine effectiveness in controlling smaller European elm bark beetles attracted to Multilure-baited surfaces. The experiment was a 5 x 3 x 8 factorial design. The treatment factors were 5 chemical concentrations (1, 3, 6, 12, and 18 or 24%; Baygon 1, 3,6, and 12%), 3 beetle exposure times (5, 20, and 60 sec), and 8 bioassay periods (every 2 weeks for 16 weeks). Each combination was replicated 3 times. Concentrations were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1984
1984
1984
1984

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Studies that compared various insecticides have uniformly concluded that chlorpyrifos and carbaryl were more toxic than methoxychlor to European elm bark beetles (Barger 1978;Page and Green 1978;Rabaglia 1980;Brown and Eads 1982). However, methoxychlor was observed to have a potent repellant effect (Doane 1962) and to be more durable on plywood surfaces than carbaryl and chlorpyrifos (Barger 1978). Lack of complete twig protection in methoxychlor-treated trees was shown to be mainly the result of incomplete coverage (Cuthbert et al 1973).…”
mentioning
confidence: 99%
“…Studies that compared various insecticides have uniformly concluded that chlorpyrifos and carbaryl were more toxic than methoxychlor to European elm bark beetles (Barger 1978;Page and Green 1978;Rabaglia 1980;Brown and Eads 1982). However, methoxychlor was observed to have a potent repellant effect (Doane 1962) and to be more durable on plywood surfaces than carbaryl and chlorpyrifos (Barger 1978). Lack of complete twig protection in methoxychlor-treated trees was shown to be mainly the result of incomplete coverage (Cuthbert et al 1973).…”
mentioning
confidence: 99%